2008
DOI: 10.1007/s11695-007-9355-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Disease: Predictors of Nonalcoholic Steatohepatitis and Gallbladder Disease in Morbid Obesity

Abstract: The prevalence of NASH in gallbladder disease was 18% in morbid obese population. We concluded that age, serum cholesterol, and low-density lipoprotein cholesterol levels were risk factors associated with gallbladder disease and fatty liver disease. Insulin resistance was more common in concurrent NASH and gallbladder disease. The mechanism between insulin resistance, fibrosis stage, NASH, and gallbladder disease is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
7
24
0
1
Order By: Relevance
“…Harrison et al [24] and Yatsuji et al [25] said that advanced age was related to advanced fibrosis. Singh et al [26] and Liew et al [27] found that older females were identified as independent predictors of fibrotic severity. Ong et al [12] , Helling et al [28] and Arun et al [29] stated that male gender was associated with NASH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harrison et al [24] and Yatsuji et al [25] said that advanced age was related to advanced fibrosis. Singh et al [26] and Liew et al [27] found that older females were identified as independent predictors of fibrotic severity. Ong et al [12] , Helling et al [28] and Arun et al [29] stated that male gender was associated with NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Assy et al [45] defined hypertriglyceridemia and diabetes as the only risk factors that increase the risk of fatty infiltration in hyperlipidemic patients. Liew et al [27] featured that serum cholesterol and low-density lipoprotein cholesterol levels were risk factors associated with gallbladder disease and fatty liver disease. Rodríguez-Hernández et al [33] said that diabetes and ALT correlated with histological hepatic changes.…”
mentioning
confidence: 99%
“…The fact the patient has an enzymatically and genetically proven GSDIa and presented with adenomatosis and HCC in adult age, should prompt liver specialists and oncologists to look for GSDIa in patients presenting with adenomatosis and/or HCC, even when adult. The presence of hepatocytes with swollen and pale cytoplasm is a well-known feature of GSD [11] Although glycogenated nuclei in the periportal area are known to represent a disturbance of glycogen metabolism, as is seen in, e.g., NASH [12], they have hitherto not been reported as a typical feature of GSD. Therefore, it is possible that they are related to the atypical clinical presentation of this patient.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of steatohepatitis is multifactorial. Insulin resistance, higher serum levels of cholesterol and LDL cholesterol may be important factors in the accumulation of hepatocellular fat, whereas excess intracellular fatty acids, oxidant stress, adenosine triphosphate (ATP) depletion, and mitochondrial dysfunction may be important causes of hepatocellular injury in the steatotic liver [22,23].…”
Section: Discussionmentioning
confidence: 99%